Assessment of the National Patient Safety Initiative Context and Baseline Evaluation Report I - Farley, Donna O. (RAND Corporation, 2005)
In September 2002, RAND contracted with the U.S. Agency for Healthcare Research and Quality to serve as the evaluation center for its national patient safety initiative. This report assesses the context and goals that were the foundation for the initiative, documents the baseline status of the activities being undertaken, and identifies priorities the researchers believe will have the strongest positive impact on the future of AHRQ's patient safety initiative.